Cardiac activity in the Mediterranean mussel (Mytilus galloprovincialis Lamarck, 1819) as a biomarker for assessing sea water quality in Boka Kotorska Bay, South Adriatic Sea - NIKOLIC, MARKO; KUZNETSOVA, TATIANA; KHOLODKEVICH, SERGEY; GVOZDENOVIC, SLADJANA; MANDIC, MILICA; JOKSIMOVIC, DANIJELA; TEODOROVIC, IVANA (Mediterranean Marine Science, 2019)
This paper presents the results of the sea water quality assessments based on the heart rate monitoring (cardiac responses) of indigenous Mediterranean mussel, Mytilus galloprovincialis. Mussels were sampled from three different sites in the Boka Kotorska Bay varied on anthropogenic pressure. Heart rate recovery time (Trec)and coefficient of variation of heart rate (CVHR) were tested in compliance with the standardized test procedure using a short-term reduction of water salinity as stress treatment to study adaptive potential of tested mussels. Results indicate the highest values of both parameters in Port Bijela, Trec = 77.3 ± 7.2 min; CVHR = 10%, indicating that water quality on this site is worse compare to Stoliv and Dobrota. ANOVA performed on results of Trec showed that values on Port Bijela are statistically significant higher compare to Stoliv and Dobrota. The lowest values of Trec are obtained on Stoliv (47.3 ± 3.8 min) what implies good water quality on this location. ANOVA showed that although higher values of Trec were obtained in Dobrota (53.3 ± 4.8 min) compare to Stoliv, those differences are not statistically significant. The proposed express method could help the authorities to plan and carry out contemporary activities to maintain high ecological status of marine coastal areas and to minimize significant risk to animal’s and human health in the case of suddenly occurred emergency situations in the region or none permitted wastewater discharges.